AB0740 Comparative Study of Patients with Peripheral Psoriatic Arthritis, Axial Psoriatic Arthritis and Axial Spondyloarthritis without Psoriasis. (10th June 2014) - Danve, A.; Garg, N.; Reddy, A.; Ku, J.; Deodhar, A.
Abstract : Background: Axial involvement in Psoriatic Arthritis (PsA) is reported to be between 40 -70% 1 . We aimed to compare the disease characteristics and quality of life (QoL) in patients with PsA with axial involvement (PsAax), PsA with only peripheral disease without axial involvement (PsApr), and axial spondyloarthritis patients without psoriasis (axSpA). Objectives: To compare the disease characteristics and quality of life (QoL) in patients with PsAax, PsApr, and axSpA Methods: Patients seen at Oregon Health & Sciences University with new diagnosis of PsAax between 2007 and 2012 were identified by searching electronic medical records. Age and sex matched patients with PsApr (polyarticular arthritis) and axSpA without psoriasis were identified. Demographic and clinical data was collected retrospectively. Disease activity and QoL was measured using validated measures like RAPID 3 and BASDAI. Statistical significance was estimated using Mann-Whitney, Chi square and Fisher's exact tests as applicable. Results: Twenty eight patients with PsAax were compared to age and sex matched patients with PsApr (n=26) and axSpA without psoriasis (n=29) respectively. Mean age, disease duration, BMI, BASDAI and RAPID 3 scores were similar among three groups (see Table). Smokers were more prevalent in axSpA than PsAPr patients (p=0.05). PsAax patients had more peripheral arthritis compared to axSpA patients (p=0.01 for both). Uveitis was significantly more prevalent in axSpA than the other 2 groups. Prevalence of depression was more in patients with psoriasis (PsAax and PsApr (about 40%)) compared to axSpA (24%) but did not reach statistical significance. Prevalence of fibromyalgia, inflammatory bowel disease, mean ESR and CRP were similar in all three groups. More patients in axSpA group used NSAIDs compared to PsAax group (p=0.05). DMARDs were used more often in patients with PsAax (p=0.01) and PsApr (p=0.01) than in axSpA. TNF blockers were used more often in PsAax than in axSpA group (p=0.03). Conclusions: In this comparative study between PsA patients with axial and peripheral disease and axSpA patients without psoriasis, PsAax patients had higher prevalence of peripheral arthritis compared to those with axSpA alone. Uveitis was less prevalent in PsAax and PsApr compared to axSpA patients. Depression was more prevalent in patients with psoriasis suggesting an important impact on QoL related to skin disease. References: Hanly JG, Russell ML, Gladman DD (1988) Psoriatic spondyloarthropathy: a long term prospective study. Ann Rheum Dis 47:386–393 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1322